Management of Undescended Testis in Gezira National Center for Pediatric Surgery (2009–2011) - Eltayeb, Omer Osman; Nugd, Faisal Abdalgalil; Mohammed, Osman Taha; Salman, Diaa eldinn Yaseen (Gezira Journal of Health Sciences, 2013)
Background : Undescended Testis (UDT) or Cryptorchidism is the most common genital problem encountered in paediatrics. Untreated UDT/cryptorchidism clearly has deleterious effects on the testis over time. In Gezira National Center for Pediatrics Surgery (GNCPS) UDT\Cryptorchidism had been treated since early 80s. During this period no study was taken to evaluate this condition. Methods :  This is a retro-prospective descriptive study done over a 2 year period from Oct 2009 to Oct 2011 including all patients with UDT operated on in the GNCPS. Patients were evaluated regarding the age at presentation, age at surgery, site of the UDT, location of the testes, investigations done and treatment modality. Results : A total of 232 children underwent orchidopexy for UDT in GNCPS, 81.5% of those patients were older than 2 years. Bilateral cases were 16.8% . Nonpalpable testes found in 36.6% of cases. Dartos pouch fixation was used in 79.8 % of the cases. Conclusion:  the majority of children with UDT presented at an age older than two year which reflect the delay in diagnosis due to lack of adequate neonatal examination. ملخص : خلفية : مرض الخصية المعلقة هو من اكثر الأمراض المتعلقة بالجهاز التناسلي شيوعا لدى الاطفال. عدم انزال الخصية المعلقة له اثار وخيمة على الخصية كلما تقدم الزمن. في مركز الجزيرة القومي لجراحة الاطفال يتم علاج الخصية المعلقة بانتظام منذ اوائل الثمانينات ورغما عن ذلك لم تجرى اي ابحاث لدراسة هذه الحالة. الطريقة و البحث: هذه الدراسة هي دراسة وصفية لاحقة تم اجراؤها خلال عامين ابتداء من اكتوبر 2009 حتى اكتوبر 2011 جميع المرضى الذين تم اجراء عمليات جراحية لهم لإنزال الخصية المعلقة تمت دراستهم من حيث العمر الذي حضر به للمستشفى, العمر الذي اجريت فيه العملية٬ اتجاه الخصية المعلقة ومكانها٬ الفحوصات التى اجريت له والعلاج الذي تلقاه. النتائج : خلال فترة الدراسة 232 طفل تم علاجهم في المركز 81.5% منهم كانت اعمارهم فوق السنتين %16.8  منهم كانت المشكلة بالجانبين و %36.6 منهم لم تكن الخصية محسوسة بالكشف السريري. تم استعمال التثبيت في جراب دارتوس في %79.8 من الحالات. الخلاصة : ان غالبية الحالات تحضر في عمر اكثر من عامين مما ينعكس سلبا على العلاج ويحدث هذا التأخير نتيجة لقلة الكشف على حديثي الولادة .